A Robust, Eco‐Friendly Access to Secondary Thioamides through the Addition of Organolithium Reagents to Isothiocyanates in Cyclopentyl Methyl Ether (CPME). Issue 52 (20th November 2015) - Pace, Vittorio; Castoldi, Laura; Monticelli, Serena; Safranek, Sandra; Roller, Alexander; Langer, Thierry; Holzer, Wolfgang
Abstract: The nucleophilic addition of widely available and variously functionalized organolithium reagents to isothiocyanates represents a straightforward, high‐yielding, one‐pot method to access secondary thioamides. The simple reaction conditions required and the broad scope (>50 cases examples) makes it a robust and reliable method to access both simple and complex thioamides, including enantiopure ones. Noxious and unpleasant‐smelling sulfurating agents, usually employed in the literature established methods, are avoided during the whole synthetic procedure thus, rendering the protocol highly attractive, also for sustainability aspects. Abstract : Not so stinky! A robust and highly efficient method to access a variety of functionalized secondary thioamides through the addition of organolithium reagents to isothiocyanates has been developed (see scheme; CPME=cyclopentyl methyl ether). This high yielding and simple methodology was also applicable for the synthesis of unprecedented bulkier thioamides under mild conditions. A complete retention of the enantiopurity was observed when chiral reagents were employed.